Innovative Approaches to Project Scheduling: Techniques and Tools - SUNIL KUMAR SUVVARI; DR. VIMAL DEEP SAXENA (Innovative Research Thoughts, 2024)
Project scheduling is essential to project management as it aligns project resources, costs, and duration. Thus, this research paper aims to identify and discuss new ideas in project scheduling and the tools that may be useful these days. The topics considered in the study include the AI and machine learning, cloud-based collaboration, risk-aware scheduling techniques, and lean scheduling. This paper will discuss these new methods and contrast them with conventional project scheduling methodologies to help project managers and researchers establish a baseline knowledge and understanding of current and possibly future practices in project scheduling. It compiles data from many empirical studies and industry reports to provide clues on the performance and popularity of diverse scheduling frameworks.